Regional international organizations as a strategy of autocracy: the Eurasian Economic Union and Russian foreign policy. (1st September 2018) - Libman, Alexander; Obydenkova, Anastassia V.
Abstract: This article investigates whether and how regional international organizations created by authoritarian countries can aid the regime survival of their member states. Numerous regions of the world have witnessed a proliferation of regional organizations established by powerful authoritarian states. We argue that the external influence of these organizations can affect regime survival and reinforce non-democratic regime trajectories, but in a nuanced manner. The article argues that, in addition to examining the impact of the regional organization itself, one must examine how the existence of these regional organizations changes the strategy of autocratic leading states, which—in bilateral relations with other countries—could become more eager to support authoritarian regimes of geopolitical importance. We use the case of the Eurasian Economic Union to explore various strategies of Russia, the leading state, vis-à-vis post-Soviet Eurasian countries. These strategies, however, appear only to matter for authoritarian consolidation when countries, from the Russian point of view, are on the 'front line' of geopolitical competition with the EU, and which are, therefore, important in stabilizing Russian influence. The article identifies five strategic foreign policy models of leading states which are determined by the existence of regional organizations and evaluates the benefits of these strategies for both leading and targeted states.